PROFILE ANALYSIS AND BUSINESS CHAIN MODEL OF VIRGIN COCONUT OIL IN INTEGRATED NYIUR COMMUNITY MSMEs - INHIL - Afdal, Muhammad; Anwardi, Anwardi; Harpito, Harpito; Norhiza, Fitra Lestari; Umam, Muhammad Isnaini Umam (Center for Study and Journal Management FTI UMI, 2024)
The problem faced by MSMEs is that the average sales of virgin coconut oil (VCO) are still relatively low. In addition, the problem faced by integrated Nyiur Community MSMEs is that the production process cannot keep up with existing market demand, this is due to market demand that is too large and the production process in MSMEs is limited. The purpose of this research is to identify business profiles, analyze and create business chain models. This research uses the Business Model Canvas and SWOT methods. The results showed that integrated nyiur Community MSMEs needed business improvements in the elements of Channels, customer relationships, revenue streams, key resources, key activities, key partners and cost structure. For the costumer segment and value proposition elements, no improvement is needed, only need to be maintained. The results of the swot analysis show that MSMEs have Strengths, Weaknesses, opportunities and threats and found several strategies for integrated Nyiur Community MSMEs.